The association between fracture and obesity is site-dependent: a population-based study in postmenopausal women. - Prieto-Alhambra, D; Premaor, M; Fina Avilés, F; Hermosilla, E; Martinez-Laguna, D; Carbonell-Abella, C; Nogués, X; Compston, J; Díez-Pérez, A (2012)
The association between obesity and fracture is controversial. We investigated the relationship between body mass index (BMI) and fracture at different skeletal sites in women aged ≥50 years using data from the Sistema d' Informació per al Desenvolupament de la Investigació en Atenció Primària (SIDIAP) database. SIDIAP contains the computerized medical records of >3400 general practitioners in Catalonia (northeastern Spain), with information on a representative 80% of the population (>5 million people). In 2009, 1,039,878 women aged ≥50 years were eligible, of whom 832,775 (80.1%) had a BMI measurement. These were categorized into underweight/normal (302,414 women), overweight (266,798), and obese (263,563). Fractures were ascertained using the International Classification of Diseases, 10th revision (ICD-10) codes. Multivariate Poisson regression models were fitted to adjust for age, smoking, high alcohol intake, type 2 diabetes, and oral corticosteroid use. Hip fractures were significantly less common in overweight and obese women than in normal/underweight women (rate ratio [RR] 0.77 [95% confidence interval (CI) 0.68 to 0.88], RR 0.63 [95% CI 0.64 to 0.79], p < 0.001, respectively). Pelvis fracture rates were lower in the overweight (RR 0.78 [95% CI 0.63 to 0.96], p = 0.017) and obese (RR 0.58 [95% CI 0.47 to 0.73], p < 0.001) groups. Conversely, obese women were at significantly higher risk of proximal humerus fracture than the normal/underweight group (RR 1.28 [95% CI 1.04 to 1.58], p = 0.018). Clinical spine, wrist, tibial, and multiple rib fracture rates were not significantly different between groups. An age-related increase in incidence was seen for all BMI groups at all fracture sites; obese women with hip, clinical spine, and pelvis fracture were significantly younger at the time of fracture than normal/underweight women, whereas those with wrist fracture were significantly older. The association between obesity and fracture in postmenopausal women is site-dependent, obesity being protective against hip and pelvis fractures but associated with an almost 30% increase in risk for proximal humerus fractures when compared with normal/underweight women. The reasons for these site-specific variations are unknown but may be related to different patterns of falls and attenuation of their impact by adipose tissue.